Fe3O4/Reduced Graphene Oxide Nanocomposite: Synthesis and Its Application for Toxic Metal Ion Removal - Nguyen Thi Vuong Hoan; Nguyen Thi Anh Thu; Hoang Van Duc; Nguyen Duc Cuong; Dinh Quang Khieu; Vien Vo (Journal of Chemistry)
The synthesis of reduced graphene oxide modified by magnetic iron oxide (Fe3O4/rGO) and its application for heavy metals removal were demonstrated. The obtained samples were characterized by X-ray diffraction (XRD), nitrogen adsorption/desorption isotherms, X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR), and magnetic measurement. The results showed that the obtained graphene oxide (GO) contains a small part of initial graphite as well as reduced oxide graphene. GO exhibits very high surface area in comparison with initial graphite. The morphology of Fe3O4/rGO consists of very fine spherical iron nanooxide particles in nanoscale. The formal kinetics and adsorption isotherms of As(V), Ni(II), and Pb(II) over obtained Fe3O4/rGO have been investigated. Fe3O4/rGO exhibits excellent heavy metal ions adsorption indicating that it is a potential adsorbent for water sources contaminated by heavy metals.